Batteryless mm-Wave Wireless Sensors - Gao, Hao (Analog Circuits and Signal Processing, 2018)
This book describes the PREMISS system, which enables readers to overcome the limitations of state-of-the-art battery-less wireless sensors in size, cost, robustness and range, with a system concept for a 60 GHz wireless sensor system with monolithic sensors. The authors demonstrate a system in which the wireless sensors consist of wireless power receiving, sensing and communication functions in a single chip, without external components, avoiding costly IC-interfaces that are sensitive to mechanical and thermal stress.